Raven tales. Love & war [videorecording (DVD)] (Indigenous Collection., 2017)
In this episode, Qos asks Raven (Dr. Evan Adams, Smoke Signals) to help him win the heart of Igis, a young woman who is too vain to love anyone but herself. Raven asks Qos to collect the snow from Igis's footprints, a tuft of her hair, and some of her old clothes to build a snowman. With a puff of his breath, Raven brings the snowman to life and names him Moowis, telling Qos that it will teach Igis the true meaning of love. But Qos is shocked when Igis falls in love with Moowis instead!